Total factor productivity growth decomposition and its determinants in Ethiopian manufacturing sector - Yismaw Ayelign Mengistu; Lakhwinder Singh (Discover Sustainability)
Abstract The objective of this study is to examine the performance of the manufacturing firms in terms of productivity growth by accounting for the determining factors. The findings revealed that growth in TFP has an average rate of 4.87% per year and showed significant improvement over the three policy periods (1996–2003, 2004–2010, and 2011–2015), respectively 3.6%, 4.7%, and 6.5%. Total factor productivity has been decomposed into contributing sources of technical progress (1%), scale change (− 0.14%), and technical efficiency change (4.01%). Twelve factors are identified from the literature as determinants of TFP growth. Eight of them are found to statistically affect this growth. The periods from 2004 to 2010 (high economic growth period) and from 2011 to 2015 (GTP I) have a higher TFP growth rate relative to the base period (1996–2003) and similar private ownership. In addition, labor input growth, capital intensity, and growth in average wage contributed positively to TFP growth. Importers of raw material inputs have higher TFP growth rates compared with non-importers. Tone can conclude from this finding that Ethiopian large and medium-scale manufacturing firms are low in terms of TFP growth. There are factors that enhance productivity, and there are also others that hinder improvements. Thus, strategically designed, coordinated with the firms themselves, and focused interventions are required in order to raise the real sales and value added using the existing state-of-the art technology and input combination, along with advancing the technical know-how, improving labor quality, updating, and renovating the capital input.